Farmers secure land and food thanks to ‘eyes in the skies’ - Bafana, Busani (2019)
Six years ago while wondering how best to use her engineering skills, Tanzanian ICT entrepreneur Rose Funja decided to enter an innovation competition. Years later she has turned a digital idea into a viable business that helps smallholder farmers across the East African nation access credit.